Mechanisms of Fetal T Cell Tolerance and Immune Regulation - Rackaityte, Elze; Halkias, Joanna (Frontiers in Immunology, 2020)
The developing human fetus generates both tolerogenic and protective immune responses in response to the unique requirements of gestation. Thus, a successful human pregnancy depends on a fine balance between two opposing immunological forces: the semi-allogeneic fetus learns to tolerate both self- and maternal- antigens and, in parallel, develops protective immunity in preparation for birth. This critical window of immune development bridges prenatal immune tolerance with the need for postnatal environmental protection, resulting in a vulnerable neonatal period with heightened risk of infection. The fetal immune system is highly specialized to mediate this transition and thus serves a different function from that of the adult. Adaptive immune memory is already evident in the fetal intestine. Fetal T cells with pro-inflammatory potential are born in a tolerogenic environment and are tightly controlled by both cell-intrinsic and -extrinsic mechanisms, suggesting that compartmentalization and specialization, rather than immaturity, define the fetal immune system. Dysregulation of fetal tolerance generates an inflammatory response with deleterious effects to the pregnancy. This review aims to discuss the recent advances in our understanding of the cellular and molecular composition of fetal adaptive immunity and the mechanisms that govern T cell development and function. We also discuss the tolerance promoting environment that impacts fetal immunity and the consequences of its breakdown. A greater understanding of fetal mechanisms of immune activation and regulation has the potential to uncover novel paradigms of immune balance which may be leveraged to develop therapies for transplantation, autoimmune disease, and birth-associated inflammatory pathologies.